Co-circulation of a Novel Dromedary Camel Parainfluenza Virus 3 and Middle East Respiratory Syndrome Coronavirus in a Dromedary Herd With Respiratory Tract Infections - Teng, Jade Lee Lee; Wernery, Ulrich; Lee, Hwei Huih; Fung, Joshua; Joseph, Sunitha; Li, Kenneth Sze Ming; Elizabeth, Shyna Korah; Fong, Jordan Yik Hei; Chan, Kwok-Hung; Chen, Honglin; Lau, Susanna Kar Pui; Woo, Patrick Chiu Yat (Frontiers in Microbiology, 2021)
Since the emergence of Middle East Respiratory Syndrome (MERS) in 2012, there have been a surge in the discovery and evolutionary studies of viruses in dromedaries. In this study, we investigated a herd of nine dromedary calves from Umm Al Quwain, the United Arab Emirates, that developed respiratory signs. Viral culture of the nasal swabs from the nine calves on Vero cells showed two different types of cytopathic effects (CPEs), suggesting the presence of two different viruses. Three samples showed typical CPEs of MERS coronavirus (MERS-CoV) in Vero cells, which was confirmed by partial RdRp gene sequencing. Complete genome sequencing of the three MERS-CoV strains showed that they belonged to clade B3, most closely related to another dromedary MERS-CoV isolate previously detected in Dubai. They also showed evidence of recombination between lineages B4 and B5 in ORF1ab. Another three samples showed non-typical CPEs of MERS-CoV with cell rounding, progressive degeneration and detachment. Electron microscopy revealed spherical viral particles with peplomers and diameter of about 170 nm. High-throughput sequencing and metagenomic analysis showed that the genome organization (3′-N-P-M-F-HN-L-5′) was typical of paramyxovirus. Furthermore, they possessed typical genome features similar to other viruses of the genus Respirovirus, including a conserved motif 323FAPGNYALSYAM336 in the N protein, RNA editing sites 5’-717AAAAAAGGG725-3’ and 5’-1038AGAAGAAAGAAAGG1051-3’ (mRNA sense) in the P gene with multiple polypeptides coding capacity, a nuclear localization signal sequence 245KVGRMYSVEYCKQKIEK261 in the M protein, a conserved sialic acid binding motif 252NRKSCS257 in the HN protein, conserved lengths of the leader (55 nt) and trailer (51 nt) sequences, total coding percentages (92.6-93.4%), gene-start (AGGANNAAAG), gene-end (NANNANNAAAAA) and trinucleotide intergenic sequences (CTT, mRNA sense). Phylogenetic analysis of their complete genomes showed that they were most closely related to bovine parainfluenza virus 3 (PIV3) genotype C strains. In the phylogenetic tree constructed using the complete L protein, the branch length between dromedary camel PIV3 (DcPIV3) and the nearest node is 0.04, which is >0.03, the definition used for species demarcation in the family Paramyxoviridae. Both MERS-CoV and DcPIV3 co-circulated in a dromedary herd in the Middle East. DcPIV3 is a novel species of the genus Respirovirus.